Dyspepsia in Nonsteroidal Anti-inflammatory Drugs Gastropathy - Chudahman Manan; Bambang Pontjo Priosoeryanto; Daldiyono Daldiyono; Sri Estuningsih; Min Rahminiwati (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) gastropathy is a common complication, which has characteristic symptoms of dyspepsia syndrome. Mostly, it includes epigastric discomfort with bloating and nausea. The aim of this study was to provide evidences that clinical symptoms of dyspepsia are related to macroscopic changes of gastric form in rats, which are expected to be applied in human. Method: The study was conducted in 20 white rats (Rattus norvegicus, Sprague-Dawley strain) at the Department of Pathology and Clinical Reproduction, Bogor Agricultural University between January and December 2008. The rats were divided to treatment group and control group and each group consisted of 10 rats. Acetyl salicylic acid (ASA/aspirin) was administered at 400 mg dose, diluted in distilled water and was given to the treatment group using gastric cannula, once daily for three days period; while the control group had received aquabidest only. Subsequently, necropsies were conducted for both groups, followed by macroscopic observation and measurement of sagittal and transversal diameter. Gastric incisions along the minor curvature were performed in both groups to recognize any macroscopic changes of gastric mucosa. ANOVA test was utilized for data analysis, which was followed by Duncan test when the results were significant. Results: Gastric diameters in treatment group with positive lesion were significantly different from the control group and the treatment group with negative lesion on anthrum/pylorus region, with p 0.05. Conclusion: Prominent gastric dilatation at anthrum/pylorus region found in the treatment group may become the initial cause and signs of dyspepsia in human. Keywords: NSAID gastropathy, dyspepsia, NSAIDs/aspirin, gastric dilatation